2017
DOI: 10.3390/ma10020119
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic and Synthetic Peptides with Oppositely Charged Amino Acids as Binding Sites for Mineralization

Abstract: Proteins regulate diverse biological processes by the specific interaction with, e.g., nucleic acids, proteins and inorganic molecules. The generation of inorganic hybrid materials, such as shell formation in mollusks, is a protein-controlled mineralization process. Moreover, inorganic-binding peptides are attractive for the bioinspired mineralization of non-natural inorganic functional materials for technical applications. However, it is still challenging to identify mineral-binding peptide motifs from biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 64 publications
(83 reference statements)
0
13
0
Order By: Relevance
“…Acidic nature and structural instability have been accepted as characteristic to BMRPs. , In this study, we have shown that among two peptides with unordered structure, same length, and similar sequence, the one with adjacent oppositely charged residues performs better compared to the one with acidic residues only. In addition, two peptides with relatively stable structures and adjacent oppositely charged residues perform better compared to the one with unordered structure but only acidic residues.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acidic nature and structural instability have been accepted as characteristic to BMRPs. , In this study, we have shown that among two peptides with unordered structure, same length, and similar sequence, the one with adjacent oppositely charged residues performs better compared to the one with acidic residues only. In addition, two peptides with relatively stable structures and adjacent oppositely charged residues perform better compared to the one with unordered structure but only acidic residues.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The presence and importance of adjacent oppositely charged amino acids in BMRPs and ion or inorganic-surface-binding peptides have come into attention recently. In 2017, by screening natural BMRPs in the “BioMine database for biomineralization proteins” and phage display selected ZnO- and ZrO 2 -binding peptides, Lemloh et al proposed that adjacent oppositely charged residues are a common feature in BMRPs and combinatorially selected inorganic-binding peptides . In an earlier study in 2006 on phage display selected hydroxyapatite-binding peptides, it was identified that 30% of the strong and moderate binders contained at least one pair of adjacent oppositely charged residues, while the ratio was only 2% in the weak binders .…”
Section: Introductionmentioning
confidence: 99%
“…This might be of special value for surface coatings with functional matter, and fluorescence tracing of the particles' distribution. Moreover, mineralization-guiding peptides installed on the outer nanoring rim were shown to induce a site-specific silica deposition around the bionanostructure from liquid precursors (Lemloh, Altintoprak, Wege, Weiss, & Rothenstein, 2017), which may serve as "bionic glue" to immobilize the nanoporous assemblies for example, in solid state membranes (Farajollahi et al, 2018). On this basis, a novel concept for using bionanopores with genetically engineerable selective permeability in technical environments has been proposed, for a charge-and size-discriminating detection or specific separation of molecules by help of robust pore-in-pore layouts (Altintoprak et al, 2019).…”
Section: Rods and Rodletsmentioning
confidence: 99%
“…The binding behavior of the identified peptide sequences was investigated for the three most abundant peptides: SnBP01, being LPPWKLK; peptide02 (SnBP02), being WSLSELH; and peptide08 (SnBP08), which is LHRHANL. In addition, peptide12 (SnBP12)—VGKTHAD—and peptide13 (SnBP13)—FPLHELR—which were selected due to a possible binding motif consisting of a charged–uncharged–charged amino acid sequence [23], were investigated. In order to determine the binding strength, M13 phage clones expressing only one of the selected peptides were bound to equal amounts of the SnO powder at pH 7.5 (Figure S2).…”
Section: Resultsmentioning
confidence: 99%